East Timor, Australia and regional order : intervention and its aftermath in Southeast Asia - Cotton, James, 1949- (Politics in Asia series., 2004)
This book explains the exceptional nature of the East Timor intervention of 1999, and deals with the background to the trusteeship role of the UN in building the new polity.